Avaliação da espessura do osso cortical em áreas de inserção de miniimplantes inter-radiculares em individuos de diferentes faixas etárias e padrões faciais - Centeno, Anna Carolina Teixeira (2018)
The purpose of this study was to evaluate the thickness of the cortical bone located in the buccal (maxilla and mandible) and palatine (maxilla) interradicular space of the region between the first permanent molars and second premolars (or second deciduous molars), sites where the orthodontic mini-implants are commonly inserted. The measurements were also evaluated for their association with the variables age, sex, skin color, vertical and sagittal facial pattern of the individuals studied. The sample consisted of 123 cone beam computed tomography (CBCT), whose images were imported into Dolphin software (Dolphin Imaging and Management Solutions, Chatsworth, Calif., USA), standardized and used to measure cortical bone thickness, vertical and sagittal facial pattern. The median age of the selected patients was 12.1 years. There was no statistically significant difference in individuals in the measurement of cortical thickness when comparing sex, skin color and sagittal facial pattern. Significantly greater measures were observed in patients older than 12 years at all sites evaluated. The linear regression analysis showed that with each increase in age, mean values of cortical thickness increase by 0.06mm in the mandible and, in the buccal and palatal maxilla, increase 0.03mm and 0.02mm, respectively. Regarding the vertical facial pattern, brachycephalic patients had the highest mean cortical thickness in all areas studied, but a statistically significant difference was observed only in the mandibular buccal cortical bone. The variables age and vertical facial pattern showed a positive correlation with the thickness of the cortical bone.